Relics of Animism in the traditional beliefs of Kazakh and Tuvan people (the end of XIX century – the beginning of XX century): comparative analysis - Dosmurzinov , Rustem K. (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The article is devoted to the problems of studying of religious wordldview in the ethnography of Kazakh and Tuvan people. It is known that in the modern period Tuvans practices Buddhism, partly Christianity and traditional beliefs (also like several other South Siberian folks – Khakasses, Altayans, Shors), Kazakhs are Muslims of Sunni direction and the Khanafi school of thought. These peoples has common historical roots and traditional worldview, that is related with religious beliefs of ancient Turkic peoples. The religion and religious culture of ancient Turks is little-known to modern science. As is well known, new information can be obtained by different methods. That’s why the aim of this article is uncover the components of religious beliefs, existing of which is not caused by canonic Buddhism of Tuvans and Islam of Kazakhs, pre-Islamic elements in the traditional worldview of Kazakhs and pre-Buddhic relics in the beliefs of Tuvans. Theoretical and methodological basis of this are advances of ethnology in the modern emphirical and theoretical studies of religious beliefs and rites. The chronological framework of research includes the end of XIX century – the beginning of XX century. The author of article comes to conclusion that the religious beliefs of Kazakh and Tuvan peoples in the period of the end of XIX century – the beginning of XX century were syncretistic. This syncretism found explicit expression in the traditional ritualism.